MTN in Nigeria : sailing too close to the wind? - Viedge, Conrad; Urban, Angie (London : Wits Business School, 2016)
In July 2016, MTN's newly appointed CEO, Rob Shuter, was considering how it was possible that the company had been fined US$5.2 billion (R78 billion ) by the Nigerian Communications Commission (NCC) in October 2015. He also wondered what could be done to prevent a debacle of this magnitude from reoccurring. It appeared that leaders were not paying attention to the issues and, most importantly, had neglected and had failed to adhere to vital regulations.The transgression was clear. MTN had failed to ensure that subscribers had registered their SIM cards in terms of the international Regulation of Interception of Communications and Provision of Communication-Related Information Act (RICA). The situation that resulted in the NCC imposing the fine should have been obvious to MTN's leadership - but was it?
Originally published in Viedge, C., & Urban, A. (2016). MTN in Nigeria: Sailing too close to the wind? WBS-2016-14. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; MTN Group Limited; Nigerian Communications Commission; Regulation of Interception of Communications and Provision of Communication-Related Information Act (RICA); Telecommunication -- Law and legislation